COMPARISON OF PASSIVE SENTENCES IN ENGLISH AND INDONESIAN - Retno Fentari (Insititut Agama Islam Agus Salim Metro Lampung, 2022)
The difficulty of a teacher teaching a second language to students can be overcome by contrastive analysis, where it is assumed that learning a second language is influenced by mastery of the first language. The purpose of this article is to describe the level of comparison of Indonesian and English passive sentences which can provide benefits as a reference in teaching English as a second language. The research was conducted using a qualitative method, with reference to literature from Indonesian and English sources.Passive sentences in Indonesian seen from their structure use